Binomial Forms Expansion of Binomial Expressions
10/7/2013 Binomial Forms 2 Special Forms Difference of Squares (Conjugate Binomials) a 2 – b 2 = ( a – b)( a + b) Difference of n th Powers a n – b n = ( a – b)( a n–1 + a n–2 b + a n–3 b a b n–1 + b n–1 ) Polynomial Functions
10/7/2013 Binomial Forms 3 Special Forms Perfect-Square Trinomials ( a + b) 2 = a a b + b 2 ( a – b) 2 = a 2 – 2 a b + b 2 Binomial Expansion Polynomial Functions n(n – 1) 2 a n–2 b bnbn n(n–1)...(2) (n – 1)! a b n–1 ( a + b) n = a n + n a n–1 b +
10/7/2013 Binomial Forms 4 Binomial Theorem Expansion of ( a + b ) n Examples: ( a + b ) 2 = a ab + b 2 ( a + b ) 3 = a a 2 b + 3 ab 2 + b 3 ( a + b ) 4 = a a 3 b + 6 a 2 b ab 3 + b 4
10/7/2013 Binomial Forms 5 Expansion of ( a + b ) n Examples: Binomial Theorem ( a + b ) 5 = a5 +a a4ba4b a3b2a3b a2b3a2b ab 4 + 5! b5b5 = a a 4 b + 10 a 3 b a 2 b ab 4 + b 5 Note: n factorial, n!, is defined as n! = n(n – 1)(n – 2)(n – 3) and 0! ≡ 1 by definition
10/7/2013 Binomial Forms 6 Expansion of ( a + b ) n The General Case: A Binomial Theorem … + + bnbn k=0 n = ∑ (n–k)! n! k! a n–k b k (a + b)n =(a + b)n = a n + n a n–1 b a n–2 b 2 n(n – 1) 2 + Note: k=0 n ∑ akak = a 0 + a 1 + a a n
10/7/2013 Binomial Forms 7 Expansion of ( a + b ) n Pascal’s Triangle Coefficients for ( a + b ) n Binomial Theorem n = 0 n = 1 n = 2 n = 3 n = 4 n = Fibonacci Sequence Degree
10/7/2013 Binomial Forms Expansion of ( a + b ) n Pascal’s Triangle Examples: ( a + b ) 0 = Binomial Theorem ( a + b ) 1 = 1 a + 1 b ( a + b ) 2 = ( a + b ) 3 = ( a + b ) 4 = ( a + b ) 5 1 a ab + 1 b 2 1 a a 2 b + 3 ab b 3 1 a a 3 b + 6 a 2 b ab b 4 = 1 a a 4 b + 10 a 3 b a 2 b ab b 5
10/7/2013 Binomial Forms 9 Think about it !